2010
DOI: 10.1074/jbc.m110.118612
|View full text |Cite
|
Sign up to set email alerts
|

Subdomain 3 of Plasmodium falciparum VAR2CSA DBL3x Is Identified as a Minimal Chondroitin Sulfate A-binding Region

Abstract: Molecular interactions between the VAR2CSA protein, expressed on the surface of Plasmodium falciparum-infected erythrocytes, and placental chondroitin sulfate A (CSA) are primarily responsible for pregnancy-associated malaria (PAM). Interrupting these interactions may prevent or ameliorate the severity of PAM. Several of the Duffy binding-like (DBL) domains of VAR2CSA, including the DBL3x domain, have been shown to bind CSA in vitro, but a more detailed understanding of how DBL domains bind CSA is needed. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…In this study, we investigated whether DBL2X or DBL3X single-domain or subdomain 3 constructs, is the minimal CSA binding region (33), could elicit inhibitory antibodies. Previous work has suggested that the DBL2X and DBL3X domains contain CSA-binding activity, and binding activity has been mapped to the DBL3 subdomain 3 (12,24,40). However, it has been questioned whether single domains accurately recapitulate the CSA binding site in native VAR2CSA (41), because single domains have much lower binding activity and more promiscuous binding specificity than fulllength recombinant proteins (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigated whether DBL2X or DBL3X single-domain or subdomain 3 constructs, is the minimal CSA binding region (33), could elicit inhibitory antibodies. Previous work has suggested that the DBL2X and DBL3X domains contain CSA-binding activity, and binding activity has been mapped to the DBL3 subdomain 3 (12,24,40). However, it has been questioned whether single domains accurately recapitulate the CSA binding site in native VAR2CSA (41), because single domains have much lower binding activity and more promiscuous binding specificity than fulllength recombinant proteins (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…5). Previous nuclear magnetic resonance (NMR) studies have shown that the DBL3X-S3 domain can bind CSA (40), suggesting that on its own this region may have very weak binding affinity for CSA. These weakly interacting DBL3X-S3 antibodies may be sufficiently specific to effectively block parasite-IE binding to CSA.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma samples from Malian adults (n ϭ 45) were collected from a study approved by the Ethics Committee of the Faculty of Medicine, Pharmacy and Odontostomatology, University of Bamako, and the Institutional Review Board (IRB) of the National Institute of Allergy and Infectious Diseases (NIAID) (13). Individual written informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%
“…Human plasma samples were collected from adults living in three areas of malaria endemicity in Mali (29). The study was approved by the ethical review committees of the Faculty of Medicine, Pharmacy, and Dentistry at the University of Bamako (Mali) and the NIAID, National Institutes of Health (Bethesda, MD).…”
Section: Methodsmentioning
confidence: 99%